2007
DOI: 10.1007/s10551-007-9601-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Culture and Religiosity on Business Ethics: A Cross-cultural Comparison

Abstract: ethical scenarios, culture, religiosity, Malays, Chinese, Indians,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…So far, many strategies have hailed micro marketing as the new marketing model of the next millennium. This research has found that there has been a very limited amount of research that examines the cultural traits and consumer ethics of subcultures within the USA and within other countries (Rashid and Ibrahim 2008). To fill this gap and since marketers cannot afford to ignore the stunning diversity of subcultures that are reshaping the American society, this research explores the differences in consumer ethics and culture using a sample from the African American subculture.…”
mentioning
confidence: 99%
“…So far, many strategies have hailed micro marketing as the new marketing model of the next millennium. This research has found that there has been a very limited amount of research that examines the cultural traits and consumer ethics of subcultures within the USA and within other countries (Rashid and Ibrahim 2008). To fill this gap and since marketers cannot afford to ignore the stunning diversity of subcultures that are reshaping the American society, this research explores the differences in consumer ethics and culture using a sample from the African American subculture.…”
mentioning
confidence: 99%
“…Empirical studies generally support the idea that different cultures interpret, often persistently, the same ethical issues in different ways (Ford et al, 2005;Goodwin and Goodwin, 1999;Rashid and Ibrahim, 2008;Sarwono and Armstrong, 2001;White and Rhodeback, 1992). The tendency of a culture to reproduce and reinforce its own idiosyncratic beliefs is echoed by the institutional theory.…”
Section: Transplantation Of Institutional Logics and Ethical Beliefsmentioning
confidence: 94%
“…The validity of particular generative mechanisms is seldom established once and for all (Ackroyd, 2004 There has been some writing investigating the relationship between organisational culture/identity and SAW (see e.g. Barrett, 2003, Carroll et al, 2014, Parboteeah and Cullen, 2003, Vandenberghe, 2011, Sheep and Foreman, 2012, Rashid and Ibrahim, 2008. However, much of this work is either descriptive or quantitative and fails to explain why such a relationship exists.…”
Section: Conclusion and Future Research Implicationsmentioning
confidence: 99%